Using participatory videos in understanding farmers experiences with climate smart agricultural practices: reflections from Ghana - Kwapong, Nana Afranaa; Whitfield, Stephen; Ambuko, Jane; Ankrah, Daniel Adu; Swanepoel, Frans (Frontiers in Sustainable Food Systems, 2024)
Climate-smart agriculture (CSA) has gained traction as one of the effective strategies in tackling the climate crisis. Many CSA practices have been promoted by development agencies to smallholder farmers based on the assumption that farmers would adopt these innovations for their potential benefits. However, the adoption of CSA practices in Ghana and much of Africa remains low and decision making and on-farm innovation processes are poorly understood. This study seeks to provide empirical and participatory insight into how smallholder farmers innovate. Based on a novel application of a participatory video methodology, in farming communities in the Upper West Region of Ghana, that have been exposed to multiple CSA intervention programmes, the paper analyses farmers’ own self-curated accounts of experiences with CSA innovation. The findings show that farmer’s motivation to adopt CSA innovations is driven by their concerns for food security, economic gains, and the environmental impact of climate change on their farming activities and livelihood. The study reveals a mismatch between the CSA technologies and practices advanced by the development agencies and what farmers perceive as relevant and important in addressing their farming challenges. In particular, the findings show that in a pool of more than 12 CSA technologies and practices that had been promoted through three donor-driven intervention programmes in the communities, farmers selected less labour intensive, less costly, and CSA technologies and practices that fitted to their current farming practices and the local context. Agricultural extension agents served as an important information source on the CSA innovation and their practical implementation and farmers’ social groups played a crucial role in facilitating learning about the CSA technologies and practices. There is the need to integrate farmers voices using innovative methodologies such as participatory videos to better understand farmers’ experiences in the innovation process which will help inform the design of effective interventions and promote adoption of innovations aimed at enhancing the productivity of smallholder farmers and reducing environmental impacts in African food systems. By focusing on the innovations that farmers perceive as beneficial and adaptable to their local contexts, development organizations can use their resources more efficiently and promote adoption of contextually appropriate CSA innovations.